(3OjhGf GdYHOjs - (3CHhGdMSf Ydj Hf MeGO GdYHOj,J (B400 (3g` s
(3ChdgG (B:s
(3bGd CHhGdMSf jeOM CejQ GdeDefjf YdjG gd aj SDGdc QSe GdefRd GdNQH HQO dbdHc ef OGA Gdghi GdhUH s
(3BNQgG (B:s
(3aGfKfi SjOj Edqi hfGOGfj JCed dge, JLO eG JQjO aJCedJge aEPG ge NfGRjQ Ydi GdTcd, cdge s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B155 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHIBjI Gddg GdMcje GdYGeI HGdfLa (B(612) s
Keywords: (3GdCOHs